Isotope Effect on the Thermal Conductivity of Graphene. (15th August 2010) - Zhang, Hengji; Lee, Geunsik; Fonseca, Alexandre F.; Borders, Tammie L.; Cho, Kyeongjae
Abstract : The thermal conductivity (TC) of isolated graphene with different concentrations of isotope (C13 ) is studied with equilibrium molecular dynamics method at 300 K. In the limit of pure C12 or C13 graphene, TC of graphene in zigzag and armchair directions are ~630 W/mK and ~1000W/mK, respectively. We find that the TC of graphene can be maximally reduced by ~80%, in both armchair and zigzag directions, when a random distribution of C12 and C13 is assumed at different doping concentrations. Therefore, our simulation results suggest an effective way to tune the TC of graphene without changing its atomic and electronic structure, thus yielding a promising application for nanoelectronics and thermoelectricity of graphene-based nano device.